2019
DOI: 10.1017/s003329171800394x
|View full text |Cite
|
Sign up to set email alerts
|

Childhood adversities in people at ultra-high risk (UHR) for psychosis: a systematic review and meta-analysis

Abstract: Childhood adversities have been reported to be more common among individuals at ultra-high risk (UHR) for psychosis. This paper systematically reviewed and meta-analysed (i) the severity and prevalence of childhood adversities (childhood trauma exposure, bullying victimisation and parental separation or loss) among the UHR, and (ii) the association between adversities and transition to psychosis (TTP). PsycINFO, PubMed and Embase databases were searched for studies reporting childhood adversities among UHR ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 70 publications
3
34
0
2
Order By: Relevance
“…Thompson et al (2009) found in an ARMS sample (n = 30), that 97% had experienced at least one form of trauma-83% reported physical abuse, 67% reported emotional abuse, and 27% sexual abuse. A systematic review and metaanalysis investigating adolescents with ARMS, also found high rates of experienced emotional abuse, physical abuse, and bullying (Peh, Rapisarda, & Lee, 2018). Studies have also investigated whether childhood trauma predicts conversion to psychosis in ARMS samples and sexual trauma was the strongest predictor of transition (Bechdolf et al, 2010;Thompson et al, 2013;Varese et al, 2012).…”
Section: Childhood Trauma and Armsmentioning
confidence: 99%
“…Thompson et al (2009) found in an ARMS sample (n = 30), that 97% had experienced at least one form of trauma-83% reported physical abuse, 67% reported emotional abuse, and 27% sexual abuse. A systematic review and metaanalysis investigating adolescents with ARMS, also found high rates of experienced emotional abuse, physical abuse, and bullying (Peh, Rapisarda, & Lee, 2018). Studies have also investigated whether childhood trauma predicts conversion to psychosis in ARMS samples and sexual trauma was the strongest predictor of transition (Bechdolf et al, 2010;Thompson et al, 2013;Varese et al, 2012).…”
Section: Childhood Trauma and Armsmentioning
confidence: 99%
“…Meta-analytic studies point to the association between traumatic life events (TLEs) and the risk of psychosis [25,26] and transition to psychosis among CHR individuals [27]. Stress has also been identified as a marker for the occurrence of subclinical psychosis in a large-scale female twin study [28].…”
Section: Introductionmentioning
confidence: 99%
“…The electronic search produced 2,210 references, 289 from PUBMED, 960 from EMBASE, 598 from PsychInfo, and 363 from Web of Science. Twelve reviews relevant to the topic, with a total of 1,126 references, and cited by 1,997 papers were also identified [10,11,[21][22][23][24][25][26][27][28][29][30]. The results of the search are presented in Figure 1.…”
Section: Resultsmentioning
confidence: 99%